The Implementation of Islamic Educational Values in Addressing the Fast Fashion Phenomenon - Farhan, Syiehd Achmed (The Future of Education Journal, 2025)
The fashion needs of individuals are rapidly evolving in line with current trends, creating a demand for continuous progress in the fashion industry. As a result, people are increasingly unwilling to fall behind in the evolution of fashion items and aspire to maintain a trendy appearance. However, this phenomenon driven by consumer demand for trendy and inexpensive clothing often leads to environmental degradation, labor exploitation, and a consumerist culture that encourages wastefulness. In response to these concerns, the author conducted a literature review to explore the potential application of Islamic values in addressing the negative impacts of the fast fashion phenomenon. This research uses a qualitative descriptive analysis method and is based on library research. The findings indicate that the implementation of education grounded in Islamic values plays a crucial role in fostering strong moral and ethical awareness across all levels of society. The Islamic value concepts that can counteract the fast fashion trend include Tawassut (moderation), Qana’ah (contentment), Syukr (gratitude), and Amanah (trustworthiness). By integrating these values into the educational curriculum, it is possible to build a society that is more environmentally and socially conscious, capable of resisting the consumerist culture driven by fast fashion.